La recherche au service de l'éducation syndicale - de Laplante, Jean (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1957)
SummaryFour years ago, the National Union of Municipal Employees of the City of Montreal, affiliated to the C.C.C.L., established an education service which has made interesting and valuable efforts to improve the training of its members. This selection was taken for indirect reasons: the increasing effort towards education in trade unionism in general; the growing interest of people in education and the development of consciousness among the City Hall personnel for the urgency of education. There also were direct reasons: the vigilant action of the union itself to favour the personal development of its members; the climate reigning at the City Hall, and the attitude of the Union towards the civic authorities.Before getting into action, everyone decided that some thinking and discussion was in order; so the group responsible for educational activities was supported by the union leaders and strongly encouraged. Every member was convinced that education should promote the human person, develop his consciousness and make him accept his responsibilities. First of all, one must know oneself in order to be integrated into society; science and techniques are very useful and must not be neglected; in and of themselves, however, they are unable to shape man. For the last two years, the themes inspiring the education program have been: "Conscience and competence of the unionized civic employee", and "Development of the personal initiative and of the sense of responsibilities".To realize its objectives, the group makes use of various techniques: study circle, union paper, union meetings, and luncheon meetings; it has also added a union practices workshop and a course for professional betterment in cooperation with the University of Montreal. Almost 300 unionized civic employees attended these sessions and paid their own fees; the union offered 50 scholarships. The methods of education used are simple, and the efforts made are on a collective basis. The key to its surprising success is group work and group decision-making.A research study has been undertaken and published in order to appreciate the value of the methodological technique used and to be used successfully in the elaboration and application of an educational program for civic employees.